1982
DOI: 10.1002/jcp.1041100110
|View full text |Cite
|
Sign up to set email alerts
|

Defective basal lamina formation by transformed mammary epithelial cells: A reduced effect of collagen on basal lamina (heparan sulfate‐rich) proteoglycan degradation

Abstract: Invasive, spontaneously transformed mammary epithelial cells derived from the normal NMuMG cell line have lost the ability of their parental cells to respond in vitro to the presence of a collagen substratum by forming a continuous glycosaminoglycan (GAG)-rich basal lamina. On collagen, the cells synthesize 35S-GAG at the same rates, but the transformed cells accumulate less 35S-GAG than the normal cells because a larger fraction of their newly synthesized 35S-GAG is rapidly degraded. Chromatography of the 35S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

1983
1983
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 21 publications
0
10
1
Order By: Relevance
“…This finding contrasts with previous studies that have not (24)(25)(26)(27)(28)(29). These differences may be related to differences in cell type, cell density, collagen preparations, or the malignant potential of the cells employed.…”
Section: Resultscontrasting
confidence: 91%
See 2 more Smart Citations
“…This finding contrasts with previous studies that have not (24)(25)(26)(27)(28)(29). These differences may be related to differences in cell type, cell density, collagen preparations, or the malignant potential of the cells employed.…”
Section: Resultscontrasting
confidence: 91%
“…The reduction in EDTA-susceptible detachment of cells grown on collagen IV is also most likely due to the preference of laminin for collagen IV (43). David and Bernfield (26,27,29) have shown that mammary epithelial cells grown on collagen I display a decreased rate of degradation of basal lamina proteoglycan, whereas neoplastic transformation of these cells interferes with the capacity of collagen to decrease the rate of degradation of these macromolecules. Our observation of similar [3S]GAG turnover in cultures of the malignant melanoma line grown on collagen or uncoated plastic is in agreement with these findings and suggests that neoplastic cells might well form a less complete basal lamina, thereby facilitating local invasion and metastasis (29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When analysed for transformation-associated changes, spontaneously transformed MuMG cells that produce invasive tumours in vivo were found to produce basement-membrane heparan sulphate of lower Mr and of lower anionic charge density than the untransformed parental counterpart (David & Van den Berghe, 1983). In contrast with the parental cell line, the transformed MuMG cells respond poorly to collagen, and show weak basal lamina formation, apparently owing to an impaired ability to decrease the degradation of heparan sulphate (David & Bernfield, 1982).…”
Section: Vol 248mentioning
confidence: 97%
“…These undersulfated HSPG prevent cell matrix interactions and formation of extracellular matrix [David and Bernfield, 1982].…”
Section: Discussionmentioning
confidence: 99%